Empowering Science Teachers to Implement ESD through Project-Based Learning: A Community Service Program for Professional Development - Purnamasari, Shinta; Santika, Ayu Ratna; Lestari, Wiwit Yuli; Syarifatoha, Nawa Hilmi; Anwar, Siti Nazila; Alyatunnawal, Annisa; Safarizi, Sabrina Aprilla; Hidayat, Aceng Muhammad Rohmat; Ramdan, Raihan Muhammad (Jurnal Pengabdian Sains dan Humaniora, 2025)
The integration of Education for Sustainable Development (ESD) into science instruction remains limited in secondary schools due to teachers’ insufficient understanding and practical skills. To address this, a professional development program was conducted to enhance the capacity of junior and senior high school science teachers to implement ESD through project-based learning (PjBL). The program consisted of three phases: conceptual enrichment, on-the-job training, and microteaching. A total of 12 science teachers completed the program. During the microteaching phase, one teacher served as a model by delivering an ESD-integrated lesson to 24 students, focusing on a solar energy project. Data were collected through facilitator observations, teacher reflections, and post-program questionnaires completed by both teachers and students. The findings indicate improved teacher understanding of ESD principles, greater ability to design PjBL activities linked to sustainability goals, and increased instructional confidence. Student feedback revealed high levels of engagement, satisfaction, and awareness of sustainability issues. These outcomes suggest that structured and practice-based professional development can effectively support science teachers in integrating ESD into classroom practice. Expanding similar programs may foster transformative science education and help prepare students to take informed action on sustainability challenges.